[Comments by Susan Stuntz to the fertilizer institute regarding the public image of the tobacco industry] - SUSAN STUNTZ (Tufts Archival Research Center, 2007)
Marginalia; Memorandum from Susan Stuntz to Samuel Chicolte and Charley Powers with a the comments made by Susan Stuntz to the Fertilizer Institute regarding the image of the tobacco industry attached. Discusses the strategies that the industry employs to combat its negative image in the media.